Yasmin the fashionista - Faruqi, Saadia; Aly, Hatem (North Mankato, Minnesota : Picture Window Books, 2018)
While her parents are out to dinner, a bored Yasmin decides to try on some of her mother's clothes, including her new shalwar kameez, which gets ripped--but with the help of Nana, Nani, and a glue-gun, the garment gets fixed, and Yasmin puts on an impromptu fashion show when her parents get home.
Keywords: Muslim girls -- Juvenile fiction; Pakistani Americans -- Juvenile fiction; Muslim families -- Juvenile fiction; Clothing and dress -- Juvenile fiction; Fashion -- Juvenile fiction; Family life -- Fiction; Clothing and dress -- Fiction; Fashion -- Fiction; Muslims -- United States -- Fiction; Pakistani Americans -- Fiction